L’intellectuel face à la célébration du (bi)centenaire de la Nation argentine - Romain Magras (Les Cahiers ALHIM)
Celebrating the founding date of a nation is generally the occasion for taking stock of the past and confronting the challenges of the future. It is not unusual to see writers emerge onto the scene in roles either complementary or antagonistic to those of politicians. In so doing they take on a social function that goes beyond that of literary creators to embody the living memory of the Nation’s origins and its founding acts; they redefine national identity and temperament in an attempt to assume the role of guides, of leaders. This objective relies on a strategy to construct the figure of the author which is based on a very particular kind of rhetoric. Taking as our point of reference the role played by Leopoldo Lugones in Argentina’s Centenary Celebrations, we shall focus on the emergence of Abel Posse’s own figure on the Argentine scene in the early years of the twenty-first century, and on the link between Leopoldo Lugones’s nationalism and Abel Posse’s claim to embody it in the context of the Bicentenary.